Drastic Scintillation Yield Enhancement of YAG:Ce with Carbon Doping. Issue 14 (21st May 2018) - Sidletskiy, Oleg; Arhipov, Pavlo; Tkachenko, Sergii; Zelenskaya, Olga; Vasyukov, Sergey; Moretti, Federico; Dujardin, Christophe
Abstract : Scintillation performances of carbon‐doped YAG and YAG:Ce crystals obtained by the Czochralski method under novel conditions of Ar+CO reducing atmosphere is compared to their counterparts obtained by conventional technologies. While light yield and energy resolution in YAG crystals grown under different conditions is similar, a fast luminescence decay component of 4–6 ns is observed in YAG:C grown by the new procedure. Optimization of post‐growth thermal annealing procedure of YAG:Ce, C scintillator provides the very high light yield of 28 200 phot MeV −1, and the energy resolution of 7.8–8.5% at 662 KeV Abstract : Light yield of YAG:Ce scintillator is drastically enhanced by carbon‐doping in crystals grown under Ar+CO atmosphere. The light yield of 28 200 phot MeV −1 and the ≈8% energy resolution at 662 KeV is achieved in YAG:Ce, C after optimization of the post‐growth annealing procedure. Meanwhile, YAG:C crystals are characterized by a very fast scintillation decay time of 4.8 ns.